The WACDT, a modern vigilance task for network defense - Guidetti, Oliver A.; Speelman, Craig P.; Bouhlas, Peter (Frontiers in Neuroergonomics, 2023)
Vigilance decrement refers to a psychophysiological decline in the capacity to sustain attention to monotonous tasks after prolonged periods. A plethora of experimental tasks exist for researchers to study vigilance decrement in classic domains such as driving and air traffic control and baggage security; however, the only cyber vigilance tasks reported in the research literature exist in the possession of the United States Air Force (USAF). Moreover, existent cyber vigilance tasks have not kept up with advances in real-world cyber security and consequently no longer accurately reflect the cognitive load associated with modern network defense. The Western Australian Cyber Defense Task (WACDT) was designed, engineered, and validated. Elements of network defense command-and-control consoles that influence the trajectory of vigilance can be adjusted within the WACDT. These elements included cognitive load, event rate, signal salience and workload transitions. Two forms of the WACDT were tested. In static trials, each element was adjusted to its maximum level of processing difficulty. In dynamic trials, these elements were set to increase from their minimum to their maximum values. Vigilance performance in static trials was shown to improve over time. In contrast, dynamic WACDT trials were characterized by vigilance performance declines. The WACDT provides the civilian human factors research community with an up-to-date and validated vigilance task for network defense accessible to civilian researchers.